Biotechnological Applications of Polyhydroxyalkanoates 2019
DOI: 10.1007/978-981-13-3759-8_12
|View full text |Cite
|
Sign up to set email alerts
|

Novel Biocontrol Agents: Short Chain Fatty Acids and More Recently, Polyhydroxyalkanoates

Abstract: Antibiotic resistance is a risk which has gradually become common knowledge.Steps are being actively taken to limit the use of antibiotics. The meat industry (poultry, piggery and sea food) are prone to infections. Containing these infections becomes cardinal for the meat which is ultimately meant for human consumption. Alternatives are therefore sought. Two alternatives which show promising pathogen containment are short chain fatty acids (SCFA) and Polyhydroxyalkanoates (PHA). SCFA are known to impart bacter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 72 publications
0
6
0
Order By: Relevance
“…The use of organic acids in poultry diets improved the performance, production, egg mass, feed efficiency, and resistance against several ailments (Islam 2012;Fouladi et al 2018). Additionally, several studies showed that organic acids including formic acids and propionic have antimicrobial impact against pathogenic bacteria like Coliforms, Salmonella spp., and Escherichia coli in the intestine of poultry (Ruhnke et al 2015;Gowda and Shivakumar 2019). Furthermore, Chowdhury et al (2009) observed an improvement in the immunological indices of chickens fed citric acid at 0.5%.…”
Section: Introductionmentioning
confidence: 91%
“…The use of organic acids in poultry diets improved the performance, production, egg mass, feed efficiency, and resistance against several ailments (Islam 2012;Fouladi et al 2018). Additionally, several studies showed that organic acids including formic acids and propionic have antimicrobial impact against pathogenic bacteria like Coliforms, Salmonella spp., and Escherichia coli in the intestine of poultry (Ruhnke et al 2015;Gowda and Shivakumar 2019). Furthermore, Chowdhury et al (2009) observed an improvement in the immunological indices of chickens fed citric acid at 0.5%.…”
Section: Introductionmentioning
confidence: 91%
“…Due to this favorable PHA biodegradability property, PHA application has been extended to the aquaculture industry. Because PHB is a biodegradable, insoluble polymer of the SCFA (3-HB), which is known as a biocontrol agent in commercial aquaculture, it has been suggested that PHB could be up taken more efficiently by filter-feeding aquatic animals and replace soluble 3-HB. PHB could be later biodegraded in the animal gut to inhibit pathogens and improve the growth and immune system of aquatic animals .…”
Section: Structures Classification and Applications Of Polyhydroxyalk...mentioning
confidence: 99%
“…18 However, this kind of PHA/PHB use is restricted by several factors, including expensive PHA production processes, downstream polymer extraction and purification, high-quality polymer requirements to meet consumer needs, and fierce competition with traditional petroleum-based plastics. 12 Accordingly, the application of PHA/PHB has been extended as a novel biocontrol agent to prevent disease outbreaks in aquaculture, 19 where minor variations in polymer properties are not regarded as problematic.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several other studies showed that propionic and formic acids have a microbial effect against Coliforms, Salmonella spp. and E. coli in the gastrointestinal tract of bird (Ruhnke et al 2015;Gowda and Shivakumar 2019). Regassa and Nyachoti (2018) stated that dietary addition of butyric acid can reduce the infection of Salmonella Enteritidis in the gut of birds.…”
Section: Caecal Microbiotamentioning
confidence: 99%
“…Subsequently, organic acids improve the growth rate, feed efficiency, and resistance against several diseases (Ricke 2003;Islam 2012). Furthermore, in broilers, formic acid was supplemented in the feed and water with the aim of improving performance indices and intestinal microbiota (Ruhnke et al 2015;Gowda and Shivakumar 2019). Also, Chowdhury et al (2009) found that an improvement in the immunological parameters of broilers fed 0.5% citric acid; Abdel-Fattah et al (2008) observed a similar improve in the immune function of chickens due to organic acids supplementation.…”
Section: Introductionmentioning
confidence: 99%